2003
DOI: 10.1016/s0046-8177(03)00090-x
|View full text |Cite
|
Sign up to set email alerts
|

A mission-based reporting system applied to an academic pathology department

Abstract: We report how data from the UCDavis mission-based reporting system (MBR) can be used to define contributions for each division within a Department of Pathology based on faculty rank and series, and to evaluate whether these contributions are in alignment with the missions of the department and the goals of the School's leadership. MBR summary reports were generated for each The Department of Pathology's average contribution to both the Teaching and Clinical Service missions was less than the School's average. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Literature about missions, teams, best practice, strategic management, quality management, globalization, leadership, change management, flatter structures, and the endless quest for efficiency and effectiveness overwhelmingly predominate (Goldberg, 2001;Howell, Green & Anders, 2003;Johnes, 2005;KoracKakabadse & Korac-Kakabadse, 1997;March, 1984;Odeck, 2006;Robertson, 1990;Rock et al, 2005;Savitch, 1998;Schachter, 1994;Strasser et al, 2005;Terrados, Almonacid & Hontoria, 2005;Wells et al, in press;Zajac & Bruhn, 1999), while little is said about the stuff of organizational life that directly effects the working lives of those who work in PA, especially with regard to their ability to provide support to the people they serve.…”
mentioning
confidence: 99%
“…Literature about missions, teams, best practice, strategic management, quality management, globalization, leadership, change management, flatter structures, and the endless quest for efficiency and effectiveness overwhelmingly predominate (Goldberg, 2001;Howell, Green & Anders, 2003;Johnes, 2005;KoracKakabadse & Korac-Kakabadse, 1997;March, 1984;Odeck, 2006;Robertson, 1990;Rock et al, 2005;Savitch, 1998;Schachter, 1994;Strasser et al, 2005;Terrados, Almonacid & Hontoria, 2005;Wells et al, in press;Zajac & Bruhn, 1999), while little is said about the stuff of organizational life that directly effects the working lives of those who work in PA, especially with regard to their ability to provide support to the people they serve.…”
mentioning
confidence: 99%
“…As we undertook the development of our PVU database, we found that, in 2003, there was a paucity of information relative to pathology. At that time Howell et al [1,2] had described the use of Web-based forms developed by their health system to enter data with algorithms to calculate effort; however, their study was based almost entirely on self-reporting estimates by faculty, which were then quality controlled by the chair. In addition, the data entry fields were not pathology-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Our faculty have continual access to their database records via a personal password protected link on the department's intranet. (2) The PVU database can be made relational to other databases in the department such as teaching logs, service schedules, current faculty lists, and others, thus decreasing duplication of effort that might otherwise be spent in entering data into a document. (3) The ability to easily access and analyze longitudinal data.…”
Section: Discussionmentioning
confidence: 99%
“…No effort was made to assign relative values to educational, clinical, research, or scholarly activities - time only Yes The Impact of a Program for Systematically Recognizing and Rewarding Academic Performance Williams 2003 [ 38 ] Mixed Department 1 - Surgery 33 - 20 analyzed Implementation/Evaluation Yes: 26% very, 44% somewhat satisfied NR - implied that it did not change Trend decreased over study, BUT more faculty got incentive $ No No NR NR NR NR 22 credits 22 credits - unclear of residents or students were differentiated NR NR NR 22 credits NR 22 credits NR 22 credits NR NR 22 credits for organizing and delivering a CME conference Incentive = 1% of the practice plan’s income. No credit for teaching activities in conjunction with pt care nor for planning (a lecture) Unit of measure was a "credit" Yes A Mission-Based Reporting System Applied to an Academic Pathology Department Howell Human Path 2003 [ 39 ] Quantitative Department - but part of UC Davis roll out 1 - Pathology 29 Implementation NR NR NR NR NR NR NR NR NR NR NR NR NR NR NR NR NR NR …”
Section: Tablementioning
confidence: 99%